Penerapann Multiple Intelligences di dalam Pembelajaran Pendidikan Agama Islam - Rohman, Abdul (Darajat: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study is to find out the importance of studying in depth the theory of multiple intelligences learning and its application in madrasas. Effective learning requires a thorough understanding of the learning process, the characteristics of students at different developmental stages, individual differences, factors that influence motivation, and procedures for maintaining an orderly classroom. Gardner defines multiple intelligences as the ability to solve problems and produce products in a variety of settings and in real situations. The method used is a qualitative literature review. The conclusion is that students will more easily understand the lesson if the material is presented in accordance with the intelligence that stands out in students. Therefore, this theory needs to be understood by teachers to enrich their competencies in order to facilitate the achievement of educational goals.